PENGARUH PEMBERIAN EKSTRAK DAUN JAMBU BIJI TERHADAP PERUBAHAN INDEKS MASSA TUBUH PADA ORANG DENGAN HIV-AIDS (Studi di Kelompok Dukungan Sebaya Arjuna Plus Semarang) - Athiyah Athiyah; Siti Fatimah Pradigdo; Suyatno Suyatno (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
People with HIV-AIDS (known as ODHA in Indonesia) have decreased immune system continuously accompanied by worsening their nutritional condition stated in the Body Mass Index (IMT). Guava leaves contain flavonoids, tannins 17.4%, phenolics 575.3 mg / g, and essential oils. Guava leaf is another alternative as a source of antioxidants derived from compounds contained in guava leaves. The purpose of this study to analyze the effect of guava leaf extract to IMT on PLWHA in Arjuna Plus KDS Semarang.There by Quasi Experimental with Non Equivalent Control Group Design is used. Two groups are conducted for this study. The first is the control group without any guava leaf extract supplement, while the second group (intervention group) is given one capsule of guava leaf extract supplement/day during 20 days. 25 Respondents for each group were chosen by purposive sampling technic and have to meet its criteria. Respondents’ nutritional status are measured by body mass index and 24 hours recall of their daily nutritional intake. Different tests using Mann Whitney, Independent T-test, and Dependent T-test. The results showed no significant difference of IMT changes between the two groups (p = 0.182) but an increase in BMI by 0.07 ± 0.48 in the intervention group. IMT changes did not rise 72% in the control group and 48% in the intervention group. Factors that can not be controlled in this study is the length of a person suffering from HIV.